Circulating cell‐free fetal DNA for the detection of RHD status and sex using reflex fetal identifiers1. (6th December 2012) - Moise, K. J.; Boring, N. H.; O'Shaughnessy, R.; Simpson, L. L.; Wolfe, H. M.; Baxter, J. K.; Polzin, W.; Eddleman, K. A.; Hassan, S. S.; Skupski, D.; McLennan, G.; Paladino, T.; et al.
ABSTRACT Objective To determine the sensitivity and specificity of circulating cell‐free fetal DNA in determining the fetal RHD status and fetal sex. Methods Maternal blood was collected in each trimester of pregnancy from RhD negative nonalloimmunized women. Whole blood was centrifuged, separated into plasma and buffy coat, and frozen at –80°C. DNA analysis was conducted via allele‐specific primer extensions for exons 4, 5, and 7 of the RHD gene and for a 37‐base pair insertion in exon 4 (RHD pseudogene; psi) three Y‐chromosome sequences (SRY, DBY, and TTY2), and an extraction control (TGIFL‐like X/Y). RhD serotyping on cord blood and gender assessment of the newborns were entered into a Web‐based database. Results One hundred twenty women were enrolled. The median gestational age at the first venipuncture was 12.4 (range: 10.6–13.9) weeks with 120 samples drawn; 118 samples were drawn at 17.6 (16–20.9) weeks; and 113 samples at 28.7 (27.9–33.9) weeks. Overall accuracy for RHD was 99.1%, 99.1%, and 98.1% for each trimester and was 99.1%, 99.1%, and 100% for fetal sex determination. Conclusions Fetal RHD genotyping and sex can be very accurately determined in all three trimesters using circulating cell‐free fetal DNA in the maternal circulation. © 2012 John Wiley & Sons, Ltd.